Improving lending activities for small and medium enterprises in Military Commercial Joint Stock Bank - Hoàng, Thị Thu Hương (Đại học Quốc gia Hà Nội, 2016)
Lending activity for small and medium enterprises (SMEs) often occupies the biggest proportion of total loans in Vietnamese commercial banks. If these lending activities failed commercial banks would be in troubles, even at edge of bankruptcy. Therefore, lending activity for SMEs always attracts the consideration of bank managers as well as external investors. In this thesis, the author focuses on the SMEs lending activities in commercial banks especially in Military Bank. The objective is to understand the lending activities for SMEs in Military Bank, to find out the existing problems, causes, limitat ions of SMEs lending activities in Military Bank and to make recommendations or solutions to improve the SME lending activities for Military Bank. In Military Bank, the SMEs lending activities are relatively good as it is developing continuously and bringing huge profit for its shareholders. Nevertheless, there are still some problems in terms of the pace of credit growth and the quality of lending activities. Credit expansion in Military Bank (especial for SMEs) is, to some extent, running out of control, whereas non-performance loans ratio is on the increase. Besides that, the collateral and human resource problems should be noted with serious consideration. Some common problems of Military Bank and many commercial banks are: Credit officers do not supervise closely or understand clearly the business and operation of borrowing entrepreneurs; Test and control operation of SME department is not at the best level, having taken pass or forgotten a part of potential customers who are operating very effectively in Vietnam economy. The author remarks that Military Bank should keep SME loans growing at safer and more stable pace by changing the way to make loans and the way to select customer. Simultaneously, in order to improve the quality of lending activities, Military Bank needs to improve credit policy, quality of project due diligence, human resource, quality of information, control, supervision, debt collection, organization, management and setting a reasonable interest rate.